Strategy Formulation for Market Development of the Ready-Mix Industry in Ibu Kota Negara - Hury Wilman; Diah Pranitasari (Jurnal Ecoment Global, 2024)
Objective: This research aims to establish market development strategies for the ready-mix industry in IKN. Design/Methods/Approach: This research employs methods including literature review, data collection, and data analysis. The collected data, both primary and secondary, are processed by analyzing competitive factors in the IKN East Kalimantan area (CP Matrix), as well as internal factors (IFE Matrix) and external factors (EFE Matrix). These factors are then formulated to determine strategies using SWOT analysis, SPACE analysis, and GS Matrix. The results are further refined through the QSP Matrix to identify the strategic options to be implemented. Findings: The strategy resulting from the formulation in this research is an aggressive alternative strategy focused on market penetration, aggressive promotion, strengthening sales capabilities, and product development. This approach aims to expand the market in the IKN region, increase revenue, and achieve the company's vision. Originality/Value: No prior research has been conducted to establish market development strategies for the ready-mix industry in IKN. Practical/Policy implication: Providing strategic guidance for ready-mix industry companies to take advantage of market opportunities in the IKN region. Increasing the company's competitiveness through the implementation of aggressive strategies such as market penetration, intensive promotion, and product diversification. Supporting the achievement of the company's vision by increasing market share and revenue in developing regions. Keywords: Marketing Strategy, SWOT Matrix, SPACE Matrix, Quantitative Strategic Planning Matrix